Analisis Model Pembelajaran Two Stay Two Stray Dengan Layanan Bimbingan Kelompok Untuk Meningkatkan Komunikasi Interpersonal Siswa Di MAN Kota Palangka Raya - Romiaty Romiaty; M Wahyu Maulana (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Analysis of the Two Stay Two Stray Learning Model with Group Guidance Services to Improve Interpersonal Communication of Students in MAN Palangka Raya City. The purpose of this study was to analyze the improvement of students' interpersonal communication skills using the two stay two stray learning model in class X IS 1 MAN Kota Palangka Raya. In this study, researchers used a qualitative method with a field research approach. The subjects of this study were students of MAN Palangka Raya City. From the results of field research, it can be concluded that group guidance services using the two stay two stray learning model can improve students' interpersonal communication skills in MAN Kota Palangka Raya.Keywords: Two Stay Two Stray, Group Guidance Service, Interpersonal Communication